The global partnership for inclusive growth - Yongfu Huang; M. G. Quibria (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper investigates the determinants of inclusive growth with a focus on foreign aid. Based on the Solow growth model, a theoretical model has been developed which shows that foreign aid can stimulate inclusive growth if it is effectively used for augmenting either physical or human productive capacity. Based on UNDP's (2011) human development index, this research calculates the inequality-adjusted human development index, and uses its growth rate to measure inclusive growth. The empirical section of this paper finds evidence for a significantly positive effect of foreign aid on inclusive growth in the sample countries. It further suggests that foreign aid fosters inclusive growth effectively, particularly when aid is directed to health and education. This research has important implications for an enhanced global partnership in areas such as foreign aid to achieve an inclusive society.
Keywords: O40; I00; F35; F60; 330; inclusive growth; aid effectiveness; post-2015 development agenda; access to water; access to sanitation; primary school enrolment; limited information maximum likelihood; Solow-Modell; Entwicklungshilfe